PERKAWINAN DENGAN PEREMPUAN YANG DICERAIKAN DILUAR PENGADILAN (STUDI DI KECAMATAN ULEE KARENG BANDA ACEH) - AIYA ERNITA (PREMISE LAW JURNAL, 2015)
As human beings, they must have many problems in their married life which, without their awareness, causes a divorce. This condition occurs in the Acehnese, particularly in this research, in the people of Ulee Kareng Subdistrict, Banda Aceh. In practice, the divorcing process in Ulee Kareng often done outside the court so that it is contrary to the Law on Marriage in Indonesia; namely, Law No. 1/1974 and to the Compilation of the Islamic Law. Some factors which cause the incidence of divorce without the Court’s Ruling are economic factor, social factor, local tradition, and religious factor. In the scope of the origin of Islamic law (figh), the status of divorce without the Religious Court’s/Mahkamah Syariah’s Ruling is not contrary to Figh so that it is considered valid, and any action caused by the divorce (a new marriage and the children who are born from the new marriage) is valid. On the other hand, in the context of the Islamic law in Indonesia, the Compilation of the Islamic Law (KHI), a divorce without the Religious Court’s/Mahkamah Syariah’s Ruling is invalid because it is not in accordance with the provision on marriage as it is stipulated in Article 115 and Article 142 of KHI. The legal consequence of a divorce without the Court’s Ruling is that it can cause mudlarat (harmful) since there is no legal certainty, the wedlock between husband and wife is not broken off since the divorce is without the Court’s Ruling; in other words, their marriage is still valid. Keywords: Marriage, Divorce, Without the Court’s Ruling